A Preliminary Analysis of the Dynamics of Individual Market and Disposable Incomes - Dean Hyslop (New Zealand Government, The Treasury, 2000)
This paper reports early results from an ongoing analysis of the income dynamics of individuals, using the Inland Revenue Department's income tax database over the four- year period 1994-7. The first two parts of the paper assess the reliability of the data. The third part reports a preliminary analysis of the dynamic properties of individual incomes. Two types of analysis are used – an analysis of transitions between quintiles of market income over time – and an analysis of the covariance of individuals market and disposable incomes through time. The author finds that there is a high degree of consistency in the data, although inconsistencies point to the need for care in the handling of outliers. The analysis of dynamics suggests that, for this sample, a large fraction of the observed differences in incomes is transitory. For example, less than 50% of the differences in incomes persist after 3 years. However, if outliers are excluded, the degree of observed persistence rises quite strongly: about two-thirds of market income differences and about 60% of disposable income differences persist after three years in this sample. The latter result is in line with results typically found in US and other overseas analyses using panel data from household surveys. Further analysis, incorporating another year of data and additional modelling techniques, is underway.
Keywords: 330